Human Hepatic Cancer Stem Cells (HCSCs) Markers Correlated With Immune Infiltrates Reveal Prognostic Significance of Hepatocellular Carcinoma - Sang, Xiaopu; Wu, Fenfang; Wu, Di; Lin, Shan; Li, Jingyi; Zhao, Nan; Chen, Xiaoni; Xu, Anlong (Frontiers in Genetics, 2020)
Background: Several specific markers have been reported to be specific for hepatic cancer stem cells (HCSCs), which is usually thought to be highly associated with poor clinical outcomes. Tumor-infiltrating immune cells act as an important factor for oncogenesis. Little is known about the correlation of HCSC markers to prognosis and immune infiltrates. Methods: Expression of HCSC markers was analyzed through Oncomine database, Gene Expression Profiling Interactive Analysis (GEPIA) and Integrative Molecular Database of Hepatocellular Carcinoma (HCCDB), respectively. The prognostic effect of HCSC markers was evaluated using Kaplan-Meier plotter in association with different tumor stages, risk factors and gender. The correlation of HCSC markers to tumor-infiltrating immune cells was tested by Tumor Immune Estimation Resource (TIMER). HCSC markers related gene sets were investigated by GEPIA, with their biological functions being analyzed by Cytoscape software. Results: The expression level of 10 HCSC markers in HCC was higher than that in normal tissues in at least one database. Among them, high expression of CD24, SOX9 and SOX12 was positively correlated with poor prognosis (CD24: OS P = 0.0012, PFS P = 7.9e-05. SOX9: OS P = 0.012. SOX12: OS P = 0.0004, PFS P = 0.0013, respectively). However, the expression of CD13, CD34 and ALDH1A1 was associated with prolonged OS and PFS. SOX12 was significantly upregulated in poor prognosis of HCC patients with different conditions. Besides, total 9 HCSC markers were identified to be positively associated with immune infiltration, including SOX12. Furthermore, Toll-like receptor signaling pathway was found to be one major pathway of these HCSC markers related gene networks. Conclusion: Our results suggest that 7 upregulated HCSC markers (CD90, EpCAM, CD133, CD24, SOX9, CK19 and SOX12) are related with poor prognosis and immune infiltration in HCC. In addition, we find that high SOX12 expression remarkably affect prognosis in male HCC patients but not in female. HCC patients under viral infection or alcohol intake with increased SOX12 expression had poorer prognosis. Therefore, HCSCs markers likely play an important role in tumor related immune infiltration and SOX12 might be a potential therapeutic target in patients with HCC.